Entre conflitos e alianças : uma análise da política episcopal de Diego Gelmírez através da Historia Compostelana (séc. XII) - Monteiro, Hericly Andrade (2016)
The Historia Compostelana is a twelfth-century work that narrates the trajectory and politicians made of Diego Gelmírez, bishop and later archbishop of Santiago de Compostela between the years 1100 and 1140. Arising low Galician nobility and from a young age linked not only to the clergy as also the high nobility, Gelmírez was responsible for the movement that propelled the growth of compostelana diocese and increasing pilgrimage to the shrine dedicated to St. Thiago. It has become even more important due to its activity as bishop, because it was under his command that the See climbed the archbishopric position after annexing territories of other Churches and also promote the theft of relics. This research present examined the role played by Diego Gelmírez during the years of his activity as bishop and later of Santiago de Compostela archbishop, moments that involved not only in episcopal activity, but also in military activities, assuming many times the leading role among the Galicians, gathering troops, were for their own benefit or service of the Castilian-Leonese monarchs Urraca I (1109-1126) and Alfonso VII (1126-1157). Through the analysis of his figure expressed in compostelana history, we seek to understand the complexity of their political actions both in episcopal level, as the warrior within and how both are intertwined taking into account the conflicts and alliances present in the context of the Iberian Peninsula of its time .